Cluster-tic syndrome – 10 years until the diagnosis – A case report - Neri, Pedro; Carvalho, Pedro Rubens Araujo de; Queiroga, Morgana Feitosa de; Alcantara, Raimundo Neudson Maia; Franca, Mario Hermes Rios; Junior, Luiz Gonzaga Nogueira; Carvalho, Renata de Oliveira; Parente, Enzo Lima Alcântara; Nogueira, João Vítor Moreira; Costa, Rafaella Iughetti da (Headache Medicine, 2024)
Introduction: Cluster-Tic syndrome is characterized by the coexistence of elements from trigeminal neuralgia and cluster headache, which is a questioned entity because of its heterogeneous presentation in the cases described. Objective: Describe a case that took about 10 years to be assertively diagnosed. Case report: 30-year-old patient, doctor, history of a headache which met the criteria for low frequency episodic migraine without aura since childhood. 10 years ago, during medical school, presented an intense stabbing headache in the V2 territory on the left side of the head which lasted about 30 minutes and did not get better during the attacks, associated with agitation and ipsilateral dysautonomia symptoms such as conjunctival hyperemia, semi-ptosis and tearing. These episodes used to happen daily during about 6 weeks, presenting an inter-crisis period of about 2 years, and could be triggered by the consumption of alcoholic beverages, not depending on the quantity. Due to the prominent algic syndrome, during this 10 year period, the patient went to many neurologists for help, but did not get an assertive diagnosis and many prophylactic (amitriptyline, venlafaxine, botulinum toxin) and abortive (NSAIDs, triptans, corticosteroid) medications were prescribed , without an adequate answer in the prevention or improvement of the pain during the attacks. The patient also went through an investigation in 2018 using a brain MRI to discover a possible secondary headache, evidencing a neurovascular conflict on the opposite side of the patient’s symptom. In this context, the cluster-tic diagnosis was confirmed and the doctors tried a treatment directed to cluster headache with subcutaneous sumatriptan during the crisis, as well as verapamil during 6 weeks as a prophylactic for the attacks associated with blocking the left lesser and major occipital nerves, resulting in a positive response during both treatments. Conclusion: Due to the variety of presentations, cluster-tic syndrome can go unnoticed, leading to a diagnostic and therapeutic delay, consequently resulting in a reduced quality of life for the patient.